Peran Pendampingan dalam Perencanaan dan Inventarisasi Sumber Daya Wisata untuk Mengembangkan Desa Wisata di Desa Sukawening, Kecamatan Dramaga, Kabupaten Bogor - Esti Menur Sukanti; E.K.S. Harini; Setyardi Pratika Mulya (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Village tourism is the right concept in the development of a village and has a positive impact in improving the welfare of the local community. Sukawening Village has good potential in terms of cultural, agricultural and small and medium enterprise products. Cultural resources in this village are the activities of sarapala (archery), karinding musical instruments, pencak silat, and recitation. The natural resources are in the form of agricultural land such as rice, edamame, corn, and tubers, and there are also sheep, rabbits, and fish farming. The diversity of this potential can be used as a tourism resource to support the development of rural tourism, but the village community is still lacking of knowledge related to the initial steps to develop their village into a tourist village. This socialization activity was carried out aimed at providing knowledge to the community about the concepts and initial steps of village tourism planning and the importance of potential inventory in village spatial plans. The implementation of this activity is the existence of delivery of material and discussion forums with community leaders. The results of the implementation of the activity is that the people of Sukawening Village are expected to know the concepts and initial steps in developing their village into a tourist village. Keywords: Sukawening village, tourist village, village potential